Financial wellbeing of older Peninsular Malaysians: a gender comparison - Chan, Benjamin Yin Fah; Masud, Jariah; Tengku Abdul Hamid, Tengku Aizan; Paim, Laily (Canadian Center of Science and Education, 2010)
Longer life expectancy means older persons can live longer but it also implied that they need more money to sustain their old age. Nevertheless, research on financial wellbeing of older persons in Malaysia is few and this lead to this study highlighting some facts related to financial wellbeing of older Malaysians. A total of 1,841 older Malaysians from 60 territorial divisions in Peninsular Malaysia have been interviewed. Looking at gender differences, male and female respondents have significant differences in financial literacy, monetary attitude, financial practices as well as financial problems. Multiple regressions explained 31% variance in financial wellbeing. Female in this study are more likely to be relegated because of lower education and less net worth compared to older men. It is therefore a great challenge for older women as well as other parties to increase the financial wellbeing of older women.